2022
DOI: 10.1530/eor-22-0037
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the value of the external rotation stress test under fluoroscopy to detect syndesmotic injuries

Abstract: Purpose The aim was to conduct a systematic literature review and meta-anaylsis to analyze the diagnostic accuracy of the external rotation stress test (ERST) for syndesmotic injuries. Methods The systematic review was conducted according to the PRISMA-P guidelines (Prospero ID: CRD42021282457). Four common databases were searched from inception to September 29, 2021. Eligible were any studies facilitating the ERST under fluoroscopy in a defined state of syndesmotic instability. Syndesmotic ligament-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…This was surprising, as this test is the working horse to assess syndesmotic stability in ankle fracture cases ( 42 , 43 , 44 ). Moreover, a just recently published systematic review assessed the value of the ERST under fluoroscopy to detect subtle syndesmotic instability ( 45 ). Based on the ERST under fluoroscopy, the MCS was capable of differentiating between intact, two-ligament (AiTFL + IOL), three-ligament (AiTFL + IOL + PiTFL), and three-ligament + deltoid ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, as this test is the working horse to assess syndesmotic stability in ankle fracture cases ( 42 , 43 , 44 ). Moreover, a just recently published systematic review assessed the value of the ERST under fluoroscopy to detect subtle syndesmotic instability ( 45 ). Based on the ERST under fluoroscopy, the MCS was capable of differentiating between intact, two-ligament (AiTFL + IOL), three-ligament (AiTFL + IOL + PiTFL), and three-ligament + deltoid ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Ein knöcherner Ausriss der hinteren Syndesmose an der posterioren Tibiakante wird als posteriores malleoläres Fragment (PMF) oder Hinterkantenfragment bezeichnet, im deutschsprachigen Raum häufig als Volkmann-Fragment. 1-Band-und instabilen 2-bis 3-Band-Verletzung dienen [22].…”
Section: äTiologieunclassified
“…Dieses Fragment erlangte in den letzten Jahren zunehmend an Bedeutung in der Versorgung von Sprunggelenkfrakturen und Instabilitäten der Syndesmose. Basierend auf deren computertomografischer Diagnostik sind Klassifikationssysteme in Abhängigkeit von der Beteilung der tibiofibularen Inzisur nach Bartonicek et 1-Band-und instabilen 2-bis 3-Band-Verletzung dienen [22].…”
Section: äTiologieunclassified
“…Analogous to the hook test, a widening of the syndesmosis is recorded at the moment the force is applied. In this context, it has also been shown that the assessment of a possible widening of the medial clear space seems to be advantageous [11]. If the medial clear space is used in the intraoperative application of stress tests for the assessment of syndesmal instability, the external rotation stress test seems to be superior to the Hook test [12].…”
Section: Introductionmentioning
confidence: 99%